2016
DOI: 10.14260/jemds/2016/28
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of Enteric Fever in Children

Abstract: BACKGROUNDThe protean manifestations of enteric fever make this disease a true diagnostic challenge. Untreated enteric fever is a grueling illness that may progress to delirium, obtundation, intestinal hemorrhage, bowel perforation and death. This is a prospective study of ninety eight confirmed enteric fever children done in J N Institute of Medical Sciences, Imphal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 5 publications
4
12
1
2
Order By: Relevance
“…33 In other study they had reported relative bradycardia and hepatomegaly as the most common sign. 43 During our study, all cases were positive for Widal. Blood culture was positive in 20% of cases.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…33 In other study they had reported relative bradycardia and hepatomegaly as the most common sign. 43 During our study, all cases were positive for Widal. Blood culture was positive in 20% of cases.…”
Section: Discussionmentioning
confidence: 52%
“…35 A study done by Banu et al also reported 28% culture positive cases. 43 Due to prior use of antibiotics, the culture positive cases are decreasing. Thus, need for relay on other serological tests for diagnosis of typhoid exists.…”
Section: Discussionmentioning
confidence: 99%
“…8 However, Laishram et al reported coated tongue (80%) as the most common sign followed by Hepatomegaly (76%) and splenomegaly (38%). 12 In present study, 33.3% of the children with typhoid had white cell count less than 4000/c.mm. Absolute eosinopenia was found in 74.7% cases.…”
supporting
confidence: 44%
“…Endemicity in developing countries is attributed to the low standard of living, poor hygiene practices, poor sanitation, contaminated water sources, and lack of universal vaccination. In children, the common age group affected is between five to 19 years, but in some endemic areas of Asia, it is also common in children less than two years [ 2 ]. Clinical manifestations are non-specific, which may delay the diagnosis and treatment leading to fatal complications.…”
Section: Introductionmentioning
confidence: 99%